2019
DOI: 10.1016/j.neurobiolaging.2019.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Internal model recalibration does not deteriorate with age while motor adaptation does

Abstract: A wide range of motor function declines with aging. Motor adaptation, which occurs when participants learn to reach accurately to a target despite a perturbation, does not deviate from this rule. There are currently three major hypotheses that have been put forward to explain this age-related decline in adaptation: deterioration of internal model recalibration due to age-related cerebellar degeneration, impairment of the cognitive component of motor adaptation, and deficit in the retention of the learned movem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
137
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(158 citation statements)
references
References 87 publications
20
137
1
Order By: Relevance
“…406 12 This finding does not discount the possibility that explicit systems also contribute to residual 407 errors. For example, recent work has demonstrated that declines in explicit learning associated with 408 aging 55,56 also lead to differences in the total extent of adaptation 57 . It is tempting to suggest that these 409 differences in asymptotic performance may also reflect a change in error sensitivity, like the implicit 410 mechanism described herein.…”
mentioning
confidence: 99%
“…406 12 This finding does not discount the possibility that explicit systems also contribute to residual 407 errors. For example, recent work has demonstrated that declines in explicit learning associated with 408 aging 55,56 also lead to differences in the total extent of adaptation 57 . It is tempting to suggest that these 409 differences in asymptotic performance may also reflect a change in error sensitivity, like the implicit 410 mechanism described herein.…”
mentioning
confidence: 99%
“…Motor adaptation of reaching is a cerebellum-dependent process which likely involves proprioceptive realignment (Mostafa et al, 2015;Ostry and Gribble, 2016). While motor adaptation declines with age, this appears largely due to deficits in the cognitive aspects of this type of learning; the implicit component, internal model recalibration, is intact in older adults and may compensate for cognitive deficits (Vandevoorde and Orban de Xivry, 2019). More directly relevant to the present study, Cressman et al (2010) specifically examined the proprioceptive recalibration associated with visuomotor adaptation and found that older and younger adults realigned proprioception similarly (Cressman et al, 2010).…”
Section: Visuo-proprioceptive Realignmentmentioning
confidence: 99%
“…Changes in peripheral and central processing of sensory signals result in perceptual deficits that, along with impairments of certain cognitive and motor processes, cause widespread functional challenges in older adults (Mozolic et al, 2012). Hand dexterity, motor speed, and motor adaptation have all been found to decrease with age (Birren and Fisher, 1995;Liu et al, 2017;Vandevoorde and Orban de Xivry, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In E1, we applied the same analysis as described in Vandevoorde and Orban de Xivry (2019). The first 393 adaptation block was corrected for baseline errors by subtracting the average error of the last 18 trials 394 of baseline.…”
Section: Analysis 2: Implicit Adaptation 392mentioning
confidence: 99%
“…However, they note that the observed link would fail after 641 correction for multiple comparisons. We expanded their work by dissociating overall adaptation in an 642 implicit and an explicit component of adaptation, of which only the explicit component is known to be 643 affected with aging (Vandevoorde and Orban de Xivry, 2019). In addition, we quantified visuospatial 644 working memory with a paradigm that allowed establishing the link with the explicit component 645 .…”
Section: Explicit Adaptationmentioning
confidence: 99%